The Effect Of Facility Service Quality, Interactive Service Quality, Delivery Service, Compensation, Job Satisfaction On Employee Performance - Agusantoso, Priscilla; Wahyu Gunawan P., Andreas (Journal of Comprehensive Science, 2023)
This study aims to analyze the effect of facility service quality, interactive service quality, service delivery, compensation on job satisfaction and their impact on employee performance at PT. Shopee consisting of 150 respondents. The methodology of this research was conducting a questionnaire survey for testing the research hypothesis and using a Structure Equation Model (SEM) for data analysis. The finding resulted in the show that facility service quality, interactive service quality service delivery, compensation and job satisfaction have a positive effect on employee performance. Managerial implications should be that managers complete and fulfill the facilities provided to their employees, as well as socialize policies within the company.